1972
DOI: 10.1002/j.1537-2197.1972.tb10130.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Morphology of the Primary Vascular Systems in Some Species of Rosaceae and Leguminosae

Abstract: The structural patterns of the primary vascular systems in some species of Leguminosae and Rosaceae have been determined by tracing the longitudinal course of the vascular bundles in terminal stem segments. These systems are interpreted as consisting of sympodia, Each sympodium is composed of an axial bundle which is continuous through the length of the segment and from which arise trace bundles that supply leaves and axillary buds. A compact arrangement of vascular bundles seems to correlate with the woody. h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

1974
1974
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…Given the relatively open al., 1986). Much of the stolon material present in vascular anatomy of the clover stolon (Devadas & pastures is quite old and plays no obvious role in Beck, 1972;Thomas, 1987), and evidence for growth. Hay, Newton & Thomas (1991) found that unrestricted translocation of carbohydrate from 50 % of all stolon nodes in a white clover population single sources to multiple sinks throughout clover were located at nodal positions > 8 from the stolon plants (Chapman, Robson & Snaydon, 1991), old apex; most stolon branches first emerge from their stolon may also provide connecting pathways for the enclosing stipule when at nodal positions < 8 transfer of growth resources among plant modules (Chapman, 1983;Hay et al, 1991) and most leaves (such as the main stolon apex and stolon branches, are found at nodes 1-4 in a grazed pasture (Brock ef after Barlow 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Given the relatively open al., 1986). Much of the stolon material present in vascular anatomy of the clover stolon (Devadas & pastures is quite old and plays no obvious role in Beck, 1972;Thomas, 1987), and evidence for growth. Hay, Newton & Thomas (1991) found that unrestricted translocation of carbohydrate from 50 % of all stolon nodes in a white clover population single sources to multiple sinks throughout clover were located at nodal positions > 8 from the stolon plants (Chapman, Robson & Snaydon, 1991), old apex; most stolon branches first emerge from their stolon may also provide connecting pathways for the enclosing stipule when at nodal positions < 8 transfer of growth resources among plant modules (Chapman, 1983;Hay et al, 1991) and most leaves (such as the main stolon apex and stolon branches, are found at nodes 1-4 in a grazed pasture (Brock ef after Barlow 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Clonally growing T. repens is a system of branching stolons witb each stolon consisting of a string of nodes, all differentiated from tbe stolon apical meristern, w-bich alternate in orientation so that successive nodes produce leaves, axillary buds and roots on opposite sides of the stolon (Erith, 1924). Stolons bave four independent axial hundles, an upper and lower axial bundle on each side of the stolon, running along their length (Devadas & Beck, 1972;Thomas, 1987). When a hrancb de\-elops at a node its vascular supply arises from the two axial bundles in the parent stolon on that side, from the lower axial bundle at the node of branching and from the upper axial bundle at the first node proximal to the hrancb.…”
mentioning
confidence: 99%
“…Each leaf is supplied by three \'ascular traces (median, upper and lower) whicb arise from different axial bundles in the stolon (Erith, 1924;Devadas & Beck, 1972;Thomas, 1987). The median and upper traces arise two nodes proximal to the leaf from tbe nearside lower and the farside upper axial bundles of tbe parent stolon respectively, whereas the lower trace arises from the lower axial bundle on the far side, one node proximal to the leaf.…”
mentioning
confidence: 99%
“…are regarded as modified stem apices with determinate growth. The primary vascular patterns in stems of R. occidentalis have been determined as consisting of an open system of five well-defined sympodia with leaves arranged helically in a 2/5 phyllotaxy (Devadas & Beck, 1972). The tracing of vascular supplies through several nodes in 10/tm serial sections to study the relatedness of species and examine evolutionary trends is difficult work, and NMR microscopy, as described in the present paper, should greatly facilitate such studies.…”
Section: Resultsmentioning
confidence: 93%
“…McCully & Mallett, 1993). For over a century, the histology of vascular architecture has provided useful taxonomic markers in evolutionary studies of diverse and closely related plants (see Devadas & Beck, 1972;Fahn, 1982). However, the conventional methods needed to produce serial stained sections from large specimens and then to reconstruct key features from them in three dimensions are extremely time-consuming and labour-intensive, even when modern image analysis systems are applied (see Hibbard et al, 1993).…”
Section: N T R O D L" C T I O Nmentioning
confidence: 99%